2017
DOI: 10.17061/phrp2751745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recording of hepatitis B infection in the NSW Perinatal Data Collection with linked hepatitis B notifications

Abstract: Objective: Results of routine maternal antenatal hepatitis B (HBV) screening have been recorded in the New South Wales (NSW) Perinatal Data Collection (PDC) since January 2011. We evaluated the accuracy of this reporting in 2012, the first year that comprehensive data were available, by linking the PDC to HBV notifications.Methods: PDC records of mothers giving birth in 2012 were probabilistically linked to HBV notifications recorded in the NSW Notifiable Conditions Information Management System (NCIMS). Sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…A similar trend was noted in a UK study, which was attributed to "historic data recording issues" [17]. Further, a recent study from New South Wales found similar poor collection of HBV status on the PDC, with only a 65% capture sensitivity [19]. Overall, it seems that poor capture of HBV status is not an isolated phenomenon and may relate to why we found sub-optimal HBIG administration.…”
Section: Discussionsupporting
confidence: 86%
“…A similar trend was noted in a UK study, which was attributed to "historic data recording issues" [17]. Further, a recent study from New South Wales found similar poor collection of HBV status on the PDC, with only a 65% capture sensitivity [19]. Overall, it seems that poor capture of HBV status is not an isolated phenomenon and may relate to why we found sub-optimal HBIG administration.…”
Section: Discussionsupporting
confidence: 86%
“…Linkage to administrative data has been used previously among solid organ transplant recipients to identify incident infections 42‐44 and has been suggested as a means to passively monitor for complications of tissue allografts 45 . Routinely collected data and ICD‐10 codes have been used to identify viral infections in populations in the United States 46,47 and in Australia, 48,49 although accuracy varied. Limitations of this work include the state‐based nature of the datasets, whereby diagnoses may be missed if people have moved interstate after transplantation, and interstate donors/recipients are excluded.…”
Section: Discussionmentioning
confidence: 99%